Wie lassen sich die Sustainable Development Goals umsetzen? Herausforderungen für Städte in Deutschland und die Rolle der Planung. - Koch, Florian; Krellenberg, Kerstin; Reuter, Klaus; Libbe, Jens; Schleicher, Katharina; Krumme, Klaus; Schubert, Susanne; Kern, Kristine (Taylor & Francis, 2020)
How can the Sustainable Development Goals be implemented? Challenges for cities in Germany and the role of urban planning. The United Nations’ Agenda 2030 and the Sustainable Development Goals (SDGs) highlight the importance of cities for sustainable development globally. With SDG 11 a specific urban goal exists and also many of the other SDGs have strong ties to urban areas. However, implementing the SDGs on an urban level is not a straightforward process. This article wants to shed light in the relationship between cities and SDGs and builds up on existing literature, the practical experiences of the authors in SDG implementation as well as the work carried out by the DKN Future Earth working group on Urban Sustainability transformations. The article consists of two main parts: Firstly, we explain some challenges concerning SDG implementation in German Cities such as indicators and data availability, tradeoffs, the role and limits of urban planning and the difficulties of city-wide integration of sustainability policies. Secondly, we present potential solutions to overcoming these challenges. Prioritizing so-called impact chains, developing SDG implementation governance mechanisms and transparent negotiation processes as well as a new definition of system borders can facilitate SDG implementation. The aim of this article is also to discuss similarities and differences between the SDGs and alternative approaches such as the Local Agenda 21 and to evaluate if and how global sustainability agendas such as the SDGs can actually lead to a more sustainable development locally. In the conclusion, we acknowledge the potential of the SDGs for sustainable urban development but emphasize, that many obstacles need to be overcome on this way.
Keywords: Nachhaltige Stadtentwicklung; Nachhaltigkeit; Entwicklungsziel; Umsetzungsstrategie; Indikator; Stadtentwicklung; Stadtplanung; Integrative Planung; Urban Governance; Stadtpolitik; Agenda 2030 für nachhaltige Entwicklung; Sustainable Development Goals